ANALYSIS OF LABORATORY MANAGEMENT IN SUPPORTING SCIENCE LEARNING AT SMP NEGERI 1 ANJIR MUARA - Prasiska, Emilda; Rizkiana, Fitria; Apriani, Herlina (Universitas Negeri Makassar, 2024)
Science learning cannot only be taught in the form of concepts or theories but there needs to be practical activities in the learning process so that learning objectives can be achieved completely and comprehensively. Good science laboratory management will support the success of science learning in schools. Seeing the importance of science laboratories as a support in teaching and learning activities to achieve the expected competencies for students, science laboratories in schools need to be managed properly so that the use of science laboratory tools and functions can be achieved effectively and efficiently. This research was conducted at SMP Negeri 1 Anjir Muara with a type of research using a qualitative descriptive approach, with data collection techniques, namely observation, interviews, and documentation. Data analysis techniques used data reduction, data presentation and drawing conclusions. Based on the results of the study, it is known that of the four functions of laboratory management, namely planning, organizing, implementation, and controlling in general, they run well even though of the four functions there are two laboratory management functions that are not optimal due to limited human resources available at the school. Limited skilled human resources are one of the main obstacles in optimizing laboratory functions. Therefore, there needs to be a training program and development of teacher competencies in laboratory management, operation of practical equipment, and management of consumables.